2014
DOI: 10.3892/mmr.2014.2716
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits the proliferation of human melanoma cells by inducing G1/S cell cycle arrest and apoptosis

Abstract: Resveratrol (Res), a natural plant extract, is an effective inducer of cell apoptosis and cell cycle arrest in multiple carcinoma cell types, which has been demonstrated by its ability to inhibit the proliferation of multiple human tumor cells in vitro. Although Res possesses chemopreventive properties against several types of cancer, the molecular mechanism underlying its anticancer activity remains to be fully elucidated. The present study demonstrated that Res induced cell cycle arrest and inhibited the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 29 publications
2
29
0
1
Order By: Relevance
“…A recent study has demonstrated that treatment of human melanoma cells with resveratrol resulted in inhibition of cell proliferation by inducing G1/S cell cycle arrest and apoptosis, possibly via the p53 pathway. 19) Our present data indicated that resveratrol treatment triggered cell cycle arrest at the G1 phase possibly via the upregulation of p21 and the induction of apoptosis (Fig. 5).…”
Section: Discussionsupporting
confidence: 55%
“…A recent study has demonstrated that treatment of human melanoma cells with resveratrol resulted in inhibition of cell proliferation by inducing G1/S cell cycle arrest and apoptosis, possibly via the p53 pathway. 19) Our present data indicated that resveratrol treatment triggered cell cycle arrest at the G1 phase possibly via the upregulation of p21 and the induction of apoptosis (Fig. 5).…”
Section: Discussionsupporting
confidence: 55%
“…It was demonstrated that the change in mitochondrial outer membrane permeability could lead to apoptosis, and this change could be directly mediated by the Bcl-2 family proteins. In addition, the main activity of the Bcl-2 family proteins takes place on the mitochondrial membrane (27). In the present study, the decrease in the Bcl-2/Bax ratio might have led to a decrease in ΔΨm and subsequent activation of caspase-3 via the cytochrome c and caspase-9 pathway.…”
Section: Effects Of Corn Silk Extract On Cell Cycle Arrest In Lovo Cementioning
confidence: 54%
“…1 Some literature have illustrated that resveratrol can both inhibit tumor cell growth and promote cell apoptosis exerting its antitumor effect by means of some related cell signaling pathways. 2,3 However, poor bioavailability of resveratrol owing to factors such as low aqueous solubility, easy photodegradation and extensive first-pass metabolism hinders its further clinical application. 4 Therefore, the primary problem is how to design effective and suitable drug delivery systems (DDSs) for resveratrol to address the aforementioned shortcomings.…”
Section: Introductionmentioning
confidence: 99%